Antibacterial Activity of Ocimum Basilicum L. and Thymus Vulgaris L. Extracts against Escherichia coli as a future method for decontamination and deodorization of compost-like mixtures - Malcheva, Boyka; NASKOVA, Pavlina; GRIGOROVA-PESHEVA, Bilyana; PLAMENOV, Dragomir; BLAZHEKOVIKJ-DIMOVSKA, Dijana; NIKOLOV, Dimitar; KOLEVA, Rozalina (Edelweiss Applied Science and Technology, 2024)
Ocimum basilicum L. and Thymus vulgaris L. are natural plant sources of antimicrobial activity, which is essential to determine their qualities as biological agents against pathogenic microorganisms. The aim of the study is the analysis of the antibacterial activity of plant extracts of basil and thyme against Escherichia coli for their subsequent application in agricultural practice as additives for decontamination and deodorization of compost-like mixtures. Plant extracts from roots, stems, leaves and whole plants of basil and thyme were obtained by various methods: decoction, tincture, medicinal vinegar, medicinal wine and medicinal oil. Agar diffusion method was used to determine the antimicrobial activity of the extracts against Escherichia coli. The analyzed essential oil cultures increase the microbiological and enzymatic activity of soils. Basil extracts showed stronger antimicrobial activity against Escherichia coli than thyme extracts, differing for individual plant parts - roots variants showed higher antimicrobial activity compared to variants with leaves, stems and whole plant. In general, a lower antimicrobial activity of the plant extracts was found in the medicated wine and tincture variants (except for roots tincture), compared to the decoction, medicated vinegar and medicated oil variants. The antibacterial activity of the stem extracts depended significantly, and that of the root, leaf and whole plant extracts moderately, on the biogenicity of the soils. The analyzed essential oil cultures can be applied for decontamination (against Escherichia coli) and deodorization of compost-like mixtures. The use of basil and thyme extracts decontaminated composts from E. coli content in a repeated 4-month application.